Ultrasonography can be more informative than computed tomography for diagnosing radial head fractures: An illustrative case series - Schöll, Eckehart; Jakob, Marcel; Vach, Werner (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Ultrasonography is increasingly being discussed as an alternative to X-rays in emergency department settings. Systematic comparisons of the 2 modalities are often based on the use of computed tomography as a reference. When diagnosing patients with elbow trauma, the physicians at our emergency department experienced that ultrasonography can be more informative than cone beam computed tomography for identifying radial head fractures. Our goal is to share this experience with the scientific community.All patients diagnosed with a radial head fracture in our emergency department between January 2021 and November 2022 were identified. The images of 18 cases in which both point-of-care ultrasonography and cone beam computed tomography had been used were reviewed by us. Eight examples were selected illustrating the variation in coincidence or discrepancy between ultrasonography and computed tomography.The 8 examples illustrate that ultrasonography can be more informative than cone beam computed tomography or vice versa.The joint application of ultrasonography and computed tomography is advisable if a correct diagnosis of the extent and components of radial head fractures is of uttermost importance.
Keywords: ultrasound; Computed tomography; Radial head fracture